(untitled) (UNWE Yearbook, 2023)
Based on a comparative analysis of the different types of politicians, the statesman’s major characteristics have been identified: a strategic leader who is well aware the interests and the prestige of his own country as a mandatory norm; a powerful social integrator; manages to set priorities; has the character, the resolve and the intellectual potential to perform his mission – to guarantee the security, well-being and prosperity of his nation and state.An analysis is made of the reasons for the crisis in statehood, for the degradation of the ruling political elites, and for the lack of authentic statesmen in Bulgaria and in the European Union at the start of the 21st century.Special attention is paid to the first of its kind rating survey made in this country: The Most Successful Bulgarian Prime Ministers (1879 – 2009), which is based on a questionnaire including 56 researchers. The ranking is based on 20 indicators. The aim of the survey is to highlight the statesmen in Bulgaria’s latest history who could serve as a suit to follow for the contemporary ruling elites.The study finishes with an analysis of the role of research and cognition for state governance. Also the tradition has been outlined in UNWE in the teaching of political sciences.